2022
DOI: 10.3389/fpsyg.2022.1005055
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of transformational leadership on the relationship between deviant workplace behaviors and employee turnover intentions in China

Abstract: This study aimed to analyze the effect of deviant workplace behaviors, such as mistreatment, bullying, and incivility on employee turnover intention and identify the transformational leadership role as a moderator. The data was collected through a survey questionnaire with the help of a purposive sampling technique. A total of 318 respondents’ data was gathered from university academic and general staff in China. The results were analyzed through SPSS and structural equation modeling structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…Our research showed workplace bullying was negatively related to organizational commitment and positively related to turnover intention, which supported hypothesis 1 and was consistent with the findings of Kang [ 51 ], Qi [ 52 ] and Ren [ 53 ]. Workplace bullying leads to a range of negative effects, both on the individual (physical and mental health, post-traumatic stress disorder, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…Our research showed workplace bullying was negatively related to organizational commitment and positively related to turnover intention, which supported hypothesis 1 and was consistent with the findings of Kang [ 51 ], Qi [ 52 ] and Ren [ 53 ]. Workplace bullying leads to a range of negative effects, both on the individual (physical and mental health, post-traumatic stress disorder, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…Our research showed a positive correlation between workplace bullying and turnover intention, which supported hypothesis 1 and was consistent with the ndings of Qi [42] and Ren [43]. Muharraq E et al [44]found that workplace bullying is one of the main reasons for high attrition and low retention rates in hospitals, and its frequency is one of the best predictors of turnover intention.…”
Section: Discussionsupporting
confidence: 91%
“…Five of the studies looked into effects of bullying on various factors (e.g. turnover intention, employee health) (Anjum et al , 2019; Anjum and Muazzam, 2019; Giorgi, 2012; Malik and Björkqvist, 2019; Qi et al , 2022). Four of the studies explored the prevalence of bullying within their sample populations (Anjum and Muazzam, 2018; Anjum and Muazzam, 2019; Coyne et al , 2017; Giorgi, 2012).…”
Section: Resultsmentioning
confidence: 99%